A review on corona virus and treatment approaches with Allium sativam - Rupesh Kumar Pandey; Ravindra Kumar Pandey; Shiv Shankar Shukla; Priyanka Pandey (SpringerOpen, 2021)
Abstract Background Recently reported cases of Covid-19 globally remind us that new diseases are coming while we are unable to provide the treatment for the same. The entire world is facing this viral attack; deaths are increasing day by day as well as infected patients too. Today, in the period of this disease, can we go to the shelter of our traditional medicines? Main body In this article, we have taken medicines related to corona and conceptualized their mechanism, which gave us a chance to understand Garlic's mechanism of action, how Garlic can be a weapon in the lane with this disease. This article also tells how we can treat new diseases with our traditional herbs if no modern medicine has been discovered yet. Conclusion The present review is based on the structure of the virus and the targeted site for the drug discovery process with important constituents of Allium sativam. The review work also explains the allicin chemical constituent of Allium sativam which has targeted therapeutic sites related to Covid-19.